Acute Exacerbations of Chronic Obstructive Pulmonary Disease With a Low Procalcitonin Concentration: Impact of Antibiotic Therapy. (2nd July 2018) - Bremmer, Derek N; Moffa, Matthew A; Ma, Kiet; Bean, Holly R; Snatchko, Joseph; Trienski, Tamara L; Watson, Courtney; Walsh, Thomas L
Abstract: Background: Patients admitted with acute exacerbations of chronic obstructive pulmonary disease (AECOPD) often are prescribed antibiotics. Studies have shown that the use of procalcitonin (PCT) to guide the decision to initiate antibiotic therapy in AECOPD has resulted in less antibiotic use and similar outcomes compared with standard of care. We evaluated patients with AECOPD and low PCT concentrations to determine whether antibiotic therapy was associated with improved outcomes. Methods: We retrospectively evaluated adult patients admitted with AECOPD who had a peak PCT concentration <0.25 µg/mL. Patients were evaluated based on their antibiotic exposure: ≤24 hours vs >24 hours. We also evaluated outcomes based upon the duration of azithromycin therapy: ≤24 hours vs >24 hours. The primary outcome was all-cause 30-day readmissions. Secondary outcomes included length of stay (LOS) and COPD-related 30-day readmissions. Results: One hundred sixty-one and 195 patients received ≤24 hours vs >24 hours of antibiotic therapy, respectively. The cohort with ≤24 hours of antibiotics had a shorter LOS (2.8 vs 3.7 days; P = .01). There were no differences in all-cause 30-day readmissions (15.5% vs 17.4%; P = .63) or COPD-related 30-day readmissions (11.2% vs 12.3%; P = .74). Additionally, patients receiving ≤24 hours of azithromycin had a shorter LOS (3.0 vs 3.8 days; P = .002) and there were no differences in all-cause 30-day readmissions (16.2% vs 17.1%; P = .82) or COPD-related 30-day readmissions (11.9% vs 11.6%; P = .94). Conclusions: For adult patients hospitalized with nonsevere AECOPD and low PCT concentrations, antibiotic therapy beyond 24 hours did not improve outcomes. Abstract : Patients hospitalized with acute exacerbations of chronic obstructive pulmonary disease with a low procalcitonin concentration do not benefit from antibiotic therapy in regard to hospital length of stay or readmission rates.